Effects of Glucose Oxidase Supplementation on the Growth Performance, Antioxidative and Inflammatory Status, Gut Function, and Microbiota Composition of Broilers Fed Moldy Corn - Qu, Wenhui; Liu, Jiaguo (Frontiers in Physiology, 2021)
Background: Glucose oxidase has been widely used as a livestock feed additive, owing to its beneficial effects on growth performance and anti-oxidative ability. However, little is known about the effects of the enzyme on intestinal health. Methods: Therefore, the current study was designed to investigate the effects of dietary glucose oxidase on the growth performance, intestinal function, and microbiota composition of broilers fed mold-contaminated corn. Newly hatched Arbor Acres broilers (n=1120) were each randomly assigned to one of four groups, which were fed a basal diet, mold-contaminated diet (10% moldy corn), basal diet supplemented with 0.01% glucose oxidase, or mold-contaminated diet supplemented with 0.01% glucose oxidase. Results: The results of the experiment indicated that glucose oxidase supplementation was able to prevent the adverse effects of mold-contaminated feed on broiler growth performance, anti-oxidative status, inflammatory status, intestinal function, and microbiota composition. In regard to intestinal function, specifically, glucose oxidase supplementation improved the intestinal morphology, permeability, barrier function, and microbiota composition of broilers given mold-contaminated feed. Conclusion: These results demonstrate that glucose oxidase supplementation can be used to mitigate the adverse effects of mold-contaminated feed on broilers and indicate that intestinal microbiota may involve in the beneficial effects of glucose oxidase.